Central Bank Policies and Economic Stability in Nigeria - Ibeinmo Friday Cookey (International Journal on Economics, Finance and Sustainable Development, 2026)
This study examines the effect of Central Bank policies on economic stability in Nigeria. The study was evaluated empirically over a period of forty years (1985 to 2024). Money supply, liquidity ratio, monetary policy rate and exchange rate were used as proxies of Central Bank policies while Real Gross Domestic Product growth rate was used to proxy economic stability. The study adopted ex-post facto research design and made use of annual time series data which were mainly sourced from Central Bank of Nigeria (CBN) statistical bulletin. The major techniques of data analysis adopted include Augmented Dickey-Fuller (ADF) unit root test, bounds cointegration test and Autoregressive Distributed Lag (ARDL) approach. The ADF unit root test showed that all the variables have mixed stationarity. That is, [I(0)] and [I(1)]. The bounds cointegration test result showed that there is a cointegration (long run relationship) among all the variables. The ARDL showed that the findings of the study showed that Money supply and exchange rate have positive and significant effect on Gross Domestic Product growth rate in Nigeria both in the short-and long-run, liquidity ratio has a negative and non-significant effect on Gross Domestic Product growth rate in Nigeria both in the short and long run while monetary policy rate has a negative and significant effect on Gross Domestic Product growth rate in Nigeria in the long run. Based on the findings, the study concluded that Central Bank policies play a vital role in promoting economic stability in Nigeria. It was recommended among others that Central Bank of Nigeria (CBN) should enhance transparency and consistency in its monetary policy formulation and communication in order to promote economic stability. This is because frequent changes or unclear signals in money supply control, interest rate decisions and exchange rate management may create uncertainties in the economy.